Racial, ethnic, and age disparities in the association of mental health symptoms and polysubstance use among persons in HIV care. - Thibaut Davy-Mendez; Varada Sarovar; Tory Levine-Hall; Alexandra N Lea; Amy S Leibowitz; Mitchell N Luu; Jason A Flamm; C Bradley Hare; Jaime Dumoit Smith; Esti Iturralde; James Dilley; Michael J Silverberg; et al. (PLoS ONE, 2023)
We characterized polysubstance use burden and associations with mental health problems across demographic subgroups of PWH. In 2018-2020, as part of a primary care-based intervention study, PWH in care at three medical centers in Kaiser Permanente Northern California were screened for depression (PHQ-9≥10), anxiety (GAD-2≥3), and substance use (Tobacco, Alcohol, Prescription medication, and other Substance use [TAPS]≥1 per substance). We used Poisson regression to estimate prevalence ratios (PRs) comparing polysubstance use prevalence (TAPS≥1 for ≥2 substances) between PWH with positive screens for depression or anxiety vs. neither, among all PWH, and stratified by race/ethnicity and age (restricted to men), adjusting for sociodemographics, CD4, and HIV load. Screened PWH (N = 2865) included 92% men, 56% White, 19% Black, and 15% Hispanic PWH, with a median age of 55 years. Overall, polysubstance use prevalence was 26.4% (95% CI 24.9%-28.1%). PWH with depression or anxiety (n = 515) had an adjusted polysubstance use PR of 1.26 (1.09-1.46) vs. PWH with neither (n = 2350). Adjusted PRs were 1.47 (1.11-1.96), 1.07 (0.74-1.54), and 1.10 (0.85-1.41) among Black, Hispanic, and White men, respectively. Adjusted PRs did not differ by age group. Interventions should consider jointly addressing mental health and substance use problems and potential drivers, e.g. stigma or socioeconomic factors.